Analisis Persepsi Penonton Terhadap Modern Dance Sebagai Media Promosi Digital di Kalangan Umat Buddha - Novita Chris; Tony Wibowo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Advertising is a digital marketing strategy that can be formed from a combination of several elements that complement each other to influence audience perception. One element that is starting to be widely used today is the dance element. Advertisements with dance elements have attracted the attention of many people. The purpose of this study was to measure the audience's perception of the use of advertising with dance elements. This study is important to find out the effectiveness of this digital marketing technique. This study used a hybrid method that compares the conclusions of quantitative and qualitative methods using the help of statistical applications and structural equation modeling. Through the conclusion of the study, this study revealed that the perception of the audience's purchase intention can be influenced by the creativeness, entertainment and informativeness of the dance element advertisement. Dance creativity was also found to have a significant effect on changes in advertising value. This study also found that dance entertainment also influenced changes in attitudes towards advertising. This research provides insight for companies to measure the effectiveness of dance element advertisements.